DESAIN PENYAJIAN MATERI PERSAMAAN GARIS LURUS DI SMP BERORIENTASI KETERAMPILAN BERPIKIR TINGKAT TINGGI - Ibrahim, Ibrahim (Media Pendidikan Matematika, 2020)
The purpose of this literature studies is to gain knowledge in designing straight line equation material in middle school oriented to higher order thinking skills. The theory used in this study is constructivism in mathematics learning and the concept of higher order thinking skills. The presentation design of straight line equation material is designed through a presentation in the form of four problem situations are gradient, straight line equations, characteristics of straight line equations and applications of straight line equations. The four problem situations, based on theoretical studies, can be said to have fulfilled the three basic principles in constructing mathematical knowledge and three aspects of higher order thinking skills. The three basic principles in constructing mathematical knowledge are active student construction of mathematical knowledge, students construct new mathematical knowledge from the results of a physical and mental reflection and mathematical knowledge is formed by students through discussion and dialogue in their social learning environment. The three aspects of higher order thinking skills are deep understanding, reasoning and problem solving. The results of this literature studies can be concluded that the presentation design of straight line equations material in middle school in this study can be said to be oriented to higher order thinking skills. This is because theoretically able to generate activities that are oriented towards higher-order thinking skills, so that there is a great opportunity to equip students with the thoughts needed to form quality human resources in the 21st century.